2018
DOI: 10.1101/367979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Noninvasive Vagus Nerve Stimulation Alters the Neural and Physiological Response to Noxious Thermal Challenge

Abstract: The mechanisms by which noninvasive vagal nerve stimulation (nVNS) affect central and peripheral neural circuits that subserve pain and autonomic physiology are not clear, and thus remain an area of intense investigation. Effects of nVNS vs sham stimulation on subject responses to five noxious thermal stimuli (applied to left lower extremity), were measured in 30 healthy subjects (n=15 sham and n=15 nVNS), with fMRI and physiological galvanic skin response (GSR). With repeated noxious thermal stimuli a group ×… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 120 publications
(97 reference statements)
1
5
0
Order By: Relevance
“…Although NWR has been associated with chronic pain, it is also an experimental acute pain experience and known to increase activity in pain related areas such as those above (Apkarian et al, 2005). tVNS was shown to suppress the activity of these pain related areas in response to painful stimuli (Janner et al, 2018;Lerman et al, 2019). Similarly, in the present study, the taVNS suppressed activity in cortical areas associated with pain perception caused by nociceptive stimulation of the sural nerve, which may have resulted in increased NWR thresholds.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Although NWR has been associated with chronic pain, it is also an experimental acute pain experience and known to increase activity in pain related areas such as those above (Apkarian et al, 2005). tVNS was shown to suppress the activity of these pain related areas in response to painful stimuli (Janner et al, 2018;Lerman et al, 2019). Similarly, in the present study, the taVNS suppressed activity in cortical areas associated with pain perception caused by nociceptive stimulation of the sural nerve, which may have resulted in increased NWR thresholds.…”
Section: Discussionsupporting
confidence: 57%
“…Plastic changes in the brain can be immediate, such as synaptic activity synchronization, or relatively slow and long lasting, involving a wide range of neural circuits, suggesting that taVNS associated plasticity may also be long lasting, and related to the release of neurotransmitters and analgesic hormones (Beekwilder & Beems, 2010;Oleson, 2002;Sandkühler, 2000). In a previous study using fMRI, taVNS demonstrated sustained activity in cortical areas associated with pain processing for over 10 min (Frangos et al, 2015); moreover, insular cortical activity in response to pain was detected 11 to 17 min after taVNS (Lerman et al, 2019). Short-term taVNS in our study might induce lasting brain plasticity, potentially delaying the activation of pain-processing cortical areas.…”
Section: Discussionmentioning
confidence: 96%
“…The stimulator (Soterix, 1 × 1tES) was placed on the left cervical VN, which lasted for 8 min and was repeated at a frequency of 25 Hz (24 V for tcVNS, 4.5 V for sham), 2 mA, 0.5 ms pulse width. Previous studies have shown that stimulation of distal cervical locations using low voltage does not result in vagal excitation (Lerman et al, 2019). A 20 V nVNS placed directly on the carotid artery has been shown to activate the VN (Frangos and Komisaruk, 2017;Mourdoukoutas et al, 2018;Klaming et al, 2022).…”
Section: Tcvns Parameters and Stimulationmentioning
confidence: 98%
“…In fact, the United States Food and Drug Administration recently cleared tcVNS for acute and preventive treatment of pain associated with most forms of primary headache (28). Recent work has also explored tcVNS effects on noxious stimuli applied peripherally (e.g., leg) (12). This previous study found that participants who were stimulated using a sham device experienced a steady increase in pain scores each time the thermal stimulus was administered.…”
Section: Tcvns Counteracted Increases In Pain During Acute Opioid Wit...mentioning
confidence: 99%
“…Moreover, no pain measurements were reported from the study, though the device was developed to target pain. A more recent sham-controlled study in healthy participants of transcutaneous cervical VNS (tcVNS) found that participants who received sham stimulation experienced a steady increase in pain scores in response to repeated noxious stimuli, while those that received active tcVNS experienced a steady decrease in pain scores (12). The study also identified brain regions that responded differently to active tcVNS compared to sham stimulation-many of which are implicated in pain (13).…”
Section: Introductionmentioning
confidence: 99%